Penggunaan SAKIP Dalam Mewujudkan Good Governance Pada Kecamatan Genteng - Zahrotul Arofah; Muhammad Roisul Basyar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Government Agency Performance Accountability System (SAKIP) is a tool used by the government to fulfill its obligations to account for what has been done while carrying out organizational duties, which consists of several parts, namely strategic planning, performance planning, performance measurement, and performance reporting. As stated in Permen PAN-RB No.12 of 2015, these components include: 1) Planning; 2) Performance Measurement; 3) Performance Reporting; 4) Performance Evaluation. This research is descriptive research with a qualitative approach that has a research focus, namely: how the influence of the Government Agency Performance Accountability System and inhibiting factors in realizing Good Governance on the implementation of performance measurement. Data obtained from the results of observation, interviews and documentation at the research location. The results showed that the influence of the Government Agency Performance Accountability System (SAKIP) in realizing Good Governance on performance measurement in Genteng District can increase accountability in the management of public resources, with a clear system for measuring and reporting performance, government agencies become more open and responsible for the use of public funds. Information that is openly available can allow the public to monitor and evaluate government performance which in turn can increase public trust.